2002
DOI: 10.1103/physreve.65.066606
|View full text |Cite
|
Sign up to set email alerts
|

Singular and regular gap solitons between three dispersion curves

Abstract: A general model is introduced to describe a wave-envelope system for the situation when the linear dispersion relation has three branches, which in the absence of any coupling terms between these branches, would intersect pair-wise in three nearly-coincident points. The system contains two waves with a strong linear coupling between them, to which a third wave is then coupled. This model has two gaps in its linear spectrum. As is typical for wave-envelope systems, the model also contains a set of cubic nonline… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Such scenarios for a similar, but di erent, equation have been studied in detail in Qian and Tang (2001). Another system which admits coexistence of regular solitary waves, peakons and cuspons has been studied in Grimshaw et al (2002).…”
Section: Reduction To An Odementioning
confidence: 99%
“…Such scenarios for a similar, but di erent, equation have been studied in detail in Qian and Tang (2001). Another system which admits coexistence of regular solitary waves, peakons and cuspons has been studied in Grimshaw et al (2002).…”
Section: Reduction To An Odementioning
confidence: 99%
“…A system of three waves in the spatial domain, linearly coupled by a triple BG written on the surface of a planar nonlinear planar waveguide, was studied in Ref. [15]. This threewave system, which is formally tantamount to a model with "1.5'' cores in the temporal domain, gives rise to a rich family of solitons, which contains both regular gap solitons and stable "cuspons" and "peakons".…”
Section: Introductionmentioning
confidence: 99%
“…The investigation of compactons in a chain of dispersively nonlinear coupled oscillators was done by Pikovsky and Rosenau [17]. The relevance of compactons for applications in practical and theoretical studies should be found in the works [2,7,10,12,15,17,20] and citation therein. We quoted only several papers and obviously it is not complete.…”
Section: Introductionmentioning
confidence: 99%